Kualitas pelayanan Kesehatan di Rumah Sakit Umum Daerah (RSUD) Batara Guru Belopa Kabupaten Luwu (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed  to find out  how the quality of health services in Batara Guru Belopa Hospital in Luwu Regency. This study used quantitative descriptive with data sources consisting of primary data and secondary data. The population and research samples were 55 people (purposive sampling). Data collection techniques used observation, interview guidelines and questionnaires. Data analysis techniques used statistical frequency distribution and percentage. The results of this study showed that in general the quality of services in the Batara Guru Belopa Regional General Hospital (RUSD) had run well, in all indicators that included physical evidence, empathy, reliability, responsiveness and assurance that had been implemented by realizing the quality of health services as a matter of The main goal to get  national achievement and regional goals in improving public health to the community in Luwu Regency.